The Effect of Early Marriage E-Booklet Education on the Knowledge and Attitudes of Teenagers at SMA Negeri 5 Palu - Komang Mariasih, Ni; Ahmil; Farah Dhifa Dg Masikki, Maharani; Surianto (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Statistical agency data shows that Indonesia in the 10th ranks of child marriages in the world, about 1,220,900 children. Some factors that contribute toward increasing in early marriage include knowledge and attitudes of adolescents. So, the prevention through education is important that can be achieved through digitalization approaches such as e-booklets. Method: This type of quantitative research by using pre-experimental design with pre-test and post-test in one group pretest-postest design. The ttal of population in the study was 333 students in class X (ten). The total of sample was 34 students that taken only 10% of the population. The sampling technique used stratified random sampling technique. Result: The results showed that there was a significant increase in adolescent knowledge after receiving e-booklet education about early marriage, which the Wilcoxon statistical test results obtained a p-value = 0.000 < α = 0.05 and the results showed that there was a significant increase in adolescent attitudes after receiving e-booklet education about early marriage, which the Wilcoxon statistical test results obtained a p-value = 0.000 < α = 0.05. Conclusion: There is an impact of early marriage e-booklet education toward the knowledge and attitude of adolescents at SMA Negeri 5 Palu.